Development of Cadmium-Safe Crop Cultivars: A Mini Review. Issue 2 (3rd March 2016) - Ashrafzadeh, Seyedardalan; Leung, David W. M.
ABSTRACT: Natural variation in cadmium (Cd) uptake and accumulation has been found between different cultivars of a crop plant as well as among different plant species although Cd uptake can be influenced by environmental factors, particularly soil properties. This knowledge can be of practical importance for agricultural industry and plant breeders. For instance, in the case of crops, obviously, identification of cultivars with low Cd accumulation in their edible parts would be of particular interest. Cultivation of these cultivars even in soils with elevated Cd level would be a promising land-independent approach to minimize human dietary Cd intake, which is a food-safety concern. Low Cd crop cultivars meeting particular criteria, including acceptable yield performance, can be introduced as Cadmium-Safe Crop Cultivars (CSCCs). On the other hand, identification of high-Cd accumulating cultivars would enable the farming industry to exclude those cultivars in cropping for consumption purposes and employ them instead in phytoremediation programs.